Integrasi Total Quality Management dan Pendidikan Karakter dalam Pendidikan Inklusif SRMA 19 Bantul - Wahyu Insani; Sutrisno .; Suwadi . (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study aims to analyze the integration of Total Quality Management (TQM) and character education in inclusive education services at Sekolah Rakyat Menengah Atas (SRMA) 19 Bantul from the perspective of Imam Al-Ghazali’s educational thought. The study is grounded in the view that the quality of inclusive education is not solely determined by systemic effectiveness and academic achievement, but also by the success of moral development and ethical awareness within the school community. A qualitative descriptive approach with a field study design was employed. Data were collected through in-depth interviews, observations, and document analysis, and examined thematically by integrating TQM principles with Al-Ghazali’s concepts of tazkiyatun nafs (self-purification), riyadhah (habituation), uswah hasanah (role modeling), sabr (patience), and muhasabah (self-reflection). The findings indicate that inclusive learning adaptations are understood as expressions of proportional justice and continuous quality improvement rather than mere administrative compliance. Character education serves as the foundation of the school’s quality culture through the habituation of empathy within the boarding school environment and a layered mentoring system based on exemplary conduct. Furthermore, challenges related to limited resources are interpreted as part of an ongoing process of quality refinement oriented toward moral and character formation.